FAKTOR-FAKTOR INTEGRITAS LAPORAN KEUANGAN DALAM AUDIT - Aghnia Yolanda Wiguna, - (2020)
The research has the objective to find out the existence of the audit committee, audit tenure, also reputation of KAP on the integrity of financial statements. Sample amounted to 117 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016, 2017 and 2018 periods that were selected by purposive sampling. Multiple linear regression analysis is an analytical technique used for this study using SPSS Version 25 software. The significance level used is 5%. The results of testing obtained that (1) The audit committee has a significant influence on the integrity of financial statements, (2) Audit tenure does not have integrity on the integrity of financial statements, and (3) Reputation of KAP has a significant influence on the integrity of financial statements.